VALUATION OF SHARES OF INDUSTRIAL COMPANY - Santos Jiménez, Néstor (1998)
A business organization has started its activities as a level of a specific asset and debt structure expressed by the debt / equity ratio. As the company evolves and reported favorable results amortized debt and business owners receive the contribution expected by its committed capital. At a time determined the assets of the company is determined by the difference between assets and liabilities, which represents accounting business ownership for shareholders.